The authoritarian century : China's rise and the demise of the liberal international order - Ogden, Chris (Christopher) (Bristol University Press, 2022)
Chris Ogden argues that, as the world capitulates to China's preferred authoritarian order, other world powers are moving to this as a dominant global phenomenon, which will transform global institutions, human rights and political systems.